The Influence of Sensomotor Stimulation on Arousal Levels and Normal Children Attention in A Primary School in Depok, Indonesia - Nurjasmi, Emi; Sudarsono, Ari (International Journal of Psychosocial Rehabilitation, 2020)
Ability to follow and concentrate forms the basis for most functions - cognitive function. One type of stimulation that can improve attention is sensorimotor stimulation, which is stimulation through the general sensory innervation system (touch, taste, motion, vibration, temperature, and pain) and special sensory fibers (visual, auditory, and kinesthetic) with the aim of improving the entire central admission system in the cerebral cortex receptive. In terms of the importance of children having optimal levels of arousal and attention in a process of learning in elementary school education, it encourages researchers to conduct this research. This study is a quasi-experimental study in which researchers intervened with sensorimotor stimulation with various forms of activities that stimulate different senses. The purpose of this study is to look at the effectiveness of sensorimotor stimulation in normal children aged 6-8 years attending primary school. The study population was normal children aged 6-8 years in Primary School 01 Pasir Putih, Sawangan, Depok. The number of samples is in accordance with a population of 68 people by purposive sample using a pretest and posttest control group, which is a simple experimental design, with the initial measurement or observation before treatment is given. One group of subjects was given treatment, while the other group was given no treatment. Results showed Stroop test scores before and after treatment in group I were analyzed by the Paired Samples Test, which showed that sensorimotor stimulation produces significant changes in Stroop test scores (p < 0.05). Furthermore, there was no significant difference (p > 0.05) between group I, which was given sensorimotor stimulation, and group II, which was given free play.